The Palaeolithic of Northeast Asia : the history and results of research in 1940-1980 - Kashin, V. A. (Archaeopress Archaeology, 2023)
This volume combines details of discoveries of Palaeolithic sites in a vast region of Northeast Asia (covering mostly the northeastern part of modern Russia), and meticulous analysis of hypotheses, ideas, and concepts related to the Northeast Asian Palaeolithic.